Friend or Foe: Factor XII Deficiency Discovered Incidentally during Management of NSTEMI - Patrick J. Beck; John Benfield; Joshua Morales (Case Reports in Hematology, 2023)
Factor XII (FXII) deficiency is a rare coagulopathy that typically goes undiagnosed due to the lack of abnormal bleeding or thrombosis. However, the accompanying prolonged activated partial thromboplastin time (aPTT) can create difficulties with maintaining therapeutic anticoagulation in the setting of acute coronary syndrome (ACS). Here, we present the case of a 52-year-old man presenting with chest pain and diagnosed with an NSTEMI but also found with a prolonged baseline aPTT ultimately secondary to FXII deficiency. Here, we discuss the diagnostic work-up of an isolated prolonged aPTT to identify possible etiologies, such as FXII deficiency, and ultimately inform ACS management.